Morpho-physiological insights into rice germination under submerged conditions: Rice germination under submerged conditions - CH Afeefa; Bingiala Laloo; Mayank Rai (ORYZA-An International Journal of Rice, 2025)
Anaerobic germination (AG) refers to a seed’s natural capacity to germinate despite oxygen deficit by obtaining the necessary energy through anaerobic respiration. Assessing the genetic diversity of rice to create direct-seeded rice varieties with these traits is imperative. A collection of 60 rice genotypes from diverse regions of the North Eastern Hill Region was evaluated for characteristics related to anaerobic germination. Genotypes were submerged at an 8 cm depth for 21 days to screen for AG. Each of the parameters, including seedling vigour index, germination percentage, speed of germination, survival percentage, shoot length, root length, fresh weight, dry weight, and number of leaves, showed a highly significant genotype x treatment (anaerobic and control conditions) interaction, indicating substantial variation in the genotypes with respect to submergence. Principal Component Analysis detected a cumulative variance of 63.3% from first two PCs, of which PC1 accounted for 42.9% and PC2 for 20.4%. Four genotypes were determined to be tolerant (Lakang Baso, Sahbhangi Dhan, CAUS 107, CAUS 123), whereas the remaining were susceptible (BLM, Chakhao Poireiton, Phourel, and Mailung). The tolerant genotypes exhibited an average a-amylase activity of 228.51 mol min-1, which was substantially higher than that of the susceptible genotypes (77.15 mol min-1). A strong positive correlation was observed between a-amylase activity and survival percentage (r = 0.84), along with several other morphological parameters. Traits such as seedling vigour index, survival percentage, germination percentage, shoot length, and a-amylase activity were identified as reliable indicators for screening rice genotypes for anaerobic germination tolerance. The contrasting genotypes characterized in this study represent valuable genetic resources for future breeding programs.